2022
DOI: 10.1177/02676591221129737
|View full text |Cite
|
Sign up to set email alerts
|

The effect of relative cerebral hyperperfusion during cardiac surgery with cardiopulmonary bypass to delayed neurocognitive recovery

Abstract: Objective Delayed neurocognitive recovery (dNCR) remains a common complication after surgery and the incidence of it is determined 30–80% after cardiac surgery with cardiac bypass (CPB) in eldery patients. Many researchers have identified that neuropsychological complications emerge from insufficient cerebral perfusion. Relative cerebral hyperperfusion also disrupts cerebral autoregulation and might play a significant role in dNCR development. The aim of this study is to determine hyperperfusion in the middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…During surgery, various potential factors can also induce the development of PNCDs, including but not limited to anesthesia-related factors, intraoperative blood pressure and temperature fluctuations, and surgical trauma [39,40]. Implementing depth of anesthesia monitoring in elderly patients during surgery would be more beneficial in preventing stress responses caused by inadequate anesthesia, thereby reducing peripheral inflammation and the occurrence of short-term postoperative cognitive function changes [41].…”
Section: Risk Factors For Pncdsmentioning
confidence: 99%
“…During surgery, various potential factors can also induce the development of PNCDs, including but not limited to anesthesia-related factors, intraoperative blood pressure and temperature fluctuations, and surgical trauma [39,40]. Implementing depth of anesthesia monitoring in elderly patients during surgery would be more beneficial in preventing stress responses caused by inadequate anesthesia, thereby reducing peripheral inflammation and the occurrence of short-term postoperative cognitive function changes [41].…”
Section: Risk Factors For Pncdsmentioning
confidence: 99%
“…Ali isto tako smatraju kako i hiperperfuzija može rezultirati hiperperfuzij skim sindromom karakteriziranim porastom arterij skog tlaka, vazodilatacijom, slomom krvnomoždane barijere i nastankom cerebralnog edema. 37 Neke studije su pokazale kako uporaba NIRSa (tzv. blisko infracrvena spektroskopija), uređaja koji se koristi za monitoring regionalne cerebralne saturacije, te provođenje intervencijskih algoritama u slučaju cerebralne desaturacije, značajno snižava stupanj, tra janje i učestalost intraoperacijskih cerebralnih desatu racija, kao i nastanak novih lezija mozga utvrđenih MRom, ali bez jasnog dokaza o smanjenu učestalosti POKPa.…”
Section: Patogeneza Pokp-aunclassified
“…Previous studies have shown that successful cognitive functioning depends on adequate cerebral blood flow [4,5]. Cardiovascular diseases independently lead to cerebral blood flow disorders and cognitive impairments, and may require cardiac surgery with artificial blood circulation, which can also cause acute ischemic brain damage [6,7].…”
Section: Introductionmentioning
confidence: 99%